Conceptualization of Qualitative Interview: A Reflection from the Practice - Bhattarai, Devi Prasad (Interdisciplinary Research in Education, 2023)
This methodological reflection on ‘interview’ is based on my research work on, “An Ethnographic Study into Indigenous Knowledge and Life-based Learning of Dhimal Community”. The objective is to reflect on the steps that involve procedures based on personal experiences of developing and conducting the interview during an ethnographic field study. So, this reflection sheds light on how I carried out an ethnographic interview in the Dhimal indigenous community to generate data. The methodology employed in the field was an ethnography that engages the researcher as a participant who utilizes several methods depending upon the field's necessity. I visited research participants formally and informally at their homes and worksites to generate the data until were saturated. I maintained privacy and security that uphold the protection of their responses, and anonymity as an ethical consideration. The study reveals that ethnographic interviews oppose the pre-scheduled interview activities and take place through several negotiations and mutual understanding among the research participants depending on the context. Equally, the self-reflexivity of the researcher is crucial in every negotiating step to be followed, and such negations go beyond the formal context of the interview.